Sheep as a Potential Source of Zoonotic Cryptosporidiosis in China - Mi, Rongsheng (Appl Environ Microbiol, 2018)
In this study, we assessed the prevalence and genetic characteristics of Cryptosporidium in sheep from 10 provinces in China. Fecal samples from 1,035 sheep originating from 16 farms were collected, and 295 (28.5%) were found to be Cryptosporidium positive by nested PCR. Cryptosporidium was detected at all farms, with infection rates between 5.7% and 50.0%. Three Cryptosporidium species were identified, including Cryptosporidium xiaoi (73.2%, 216/295), Cryptosporidium ubiquitum (21.7%, 64/295), and Cryptosporidium parvum (5.1%, 15/295). The distribution of Cryptosporidium species differed by province and by farm. All three species were detected in lambs and adult sheep but the highest infection rate was found in postweaned lambs. All three species were detected in all four seasons, with the highest prevalence found in autumn. Four C. parvum subtypes (IIaA15G2R1, IIaA17G2R1, IIdA18G1, and IIdA19G1) and one C. ubiquitum subtype (XIIa) were identified. For most provinces in this study, we are not aware of a previously published description or molecular characterization of Cryptosporidium infections in sheep. This information will improve our knowledge and understanding of the epidemiology of cryptosporidiosis in China. IMPORTANCE Cryptosporidium is an important zoonotic parasite that causes diarrhea in humans and animals worldwide. Previous studies suggested geographic differences in the distribution of Cryptosporidium species in sheep. However, molecular characterization studies of Cryptosporidium species in sheep have been carried out in only a few provinces in China, and the limited data available do not reflect the real situation. In this study, five districts, covering most areas where sheep are bred in China, were selected for examination of Cryptosporidium species, and Cryptosporidium infections were detected at all farms assessed, suggesting that Cryptosporidium is widespread in sheep in China. We also found geographic differences in the distribution of Cryptosporidium species but did not detect any differences between sheep age groups or seasons. Subtyping analyses showed that all of the subtypes identified in this study have been reported in humans, suggesting that sheep may be a potential source of zoonotic cryptosporidiosis.